The Influence of pH and Temperature on the Stability of N-[(Piperidine)methylene]daunorubicin Hydrochloride and a Comparison of the Stability of Daunorubicin and Its Four New Amidine Derivatives in Aqueous Solutions - Mikołaj Piekarski; Agnieszka Dołhań; Judyta Cielecka-Piontek; Przemysław Zalewski; Witold Kycler; Aleksandra Kaczmarek; Artur Firlej; Irena Oszczapowicz; Anna Jelińska (The Scientific World Journal)
The influence of pH and temperature on the stability of N-[(piperidine)methylene]daunorubicin hydrochloride (PPD) was investigated. Degradation was studied using an HPLC method. Specific acid-base catalysis of PPD involves hydrolysis of protonated molecules of PPD catalyzed by hydrogen ions and spontaneous hydrolysis under the influence of water zwitterions, unprotonated molecules, and monoanions of PPD. The thermodynamic parameters of these reactions, energy, enthalpy, and entropy, were calculated. Also, the stability of daunorubicin and its new amidine derivatives (piperidine, morpholine, pyrrolidine, and hexahydroazepin-1-yl) in aqueous solutions was compared and discussed.